Tingkat Efisiensi Pemasaran Telur Itik Alabio dan Telur Asin di Kabupaten Hulu Sungai Utara Propinsi Kalimantan Selatan - Mahdalena Mahdalena (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2016)
This study aims to determine the efficiency level of each marketing channel of alabio duck and salted eggs in Hulu Sungai Utara Regency. The research activity was carried out in Hulu Sungai Utara Regency, in August-October 2013. The method used is survey method and interview with deliberately chosen location (purposive sampling). The efficiency analysis method uses the formula of Technical Efficiency Index and Economic Efficiency Index. Based on the results of the study, it was obtained technically and economically marketing efficiency was in channel III for the purpose of Palangkaraya and channel III for Simpang. Technically and economically marketing efficiency in marketing salted eggs is IET II channel <IEE which is 2.92 <3.8